PROGRAM BINA KELUARGA SAKINAH DALAM MENGATASI KONFLIK KELUARGA DI KELURAHAN MALINO KECAMATAN TINGGIMONCONG KABUPATEN GOWA (Fakultas Dakwah dan Komunikasi, 2021)
The purpose of this is to see the Sakinah Family Development Program in Overcoming Family Conflict in Malino Village, Tinggimoncong District, Gowa Regency. This study uses a qualitative approach with data using observation, interview, and documentation methods. The results of this study indicate that, the implementation of the Sakinah family development program in overcoming family conflicts with several coaching, including individual coaching, group coaching, and spiritual coaching. Extension efforts in overcoming family conflicts by conducting socialization of sakinah families in majelis taklim activities, courses for prospective brides, socialization of sakinah families through Friday worship activities, family counseling, and fostering adolescents of marriage age.